Tinjauan Hukum Islam Terhadap Praktik Jual Beli Tanah Kuburan (Kelurahan Bandar Jaya, Kecamatan Rantau Rasau) - Puput Indarwati; Daud Daud; Reza Okva Marwendi; Alisya Pitri; Hasna Dewi (Journal of Innovative and Creativity, 2025)
This study examines the practice of buying and selling cemetery land in Bandar Jaya Village, Rantau Rasau District, from an Islamic legal perspective. The focus of the study includes analyzing the transaction's compliance with the principles of Sharia muamalah (Islamic transactions), particularly regarding ownership, fair pricing, and the prohibition of exploitation. The research method employed descriptive qualitative methods, with data collection techniques including observation, in-depth interviews with religious leaders, local government officials, and community participants, as well as the study of related documents. The results indicate that the practice of buying and selling cemetery land in the study area is essentially permissible in Islam as long as it meets the following requirements: (1) certainty of land ownership (free from gharar), (2) a reasonable price agreement without any element of coercion, and (3) the land's use according to its function as a cemetery. However, several problems were identified, such as not everyone being able to pay the full fees and the potential for exploitation of bereaved families. This study recommends the need for socialization of Islamic law regarding cemetery land transactions and the strengthening of Sharia-based local regulations to ensure the principles of justice and the public interest.